Neonatal Haemoglobin and Haematocrit Level on Delayed Cord Clamping - Astrianti, LitaLIta R. (Indonesian Journal of Obstetrics and Gynecology, 2012)
Objectives: To assess neonatal haemoglobin and haematocrit level during delayed cord clamping on normal delivery. Methods: This was a randomised control trial with simple random sampling method. During March until June 2011, we collected blood sample from venous umbilical cord on newborn baby. Twenty babies were assigned to the first group, of which the clamping of the umbilical was delayed until 2 minutes (DCC). The other 20 babies were assigned to the second group, of which the clamping of the umbilical was performed as early as 10 second (ECC) after delivery of the whole body of the baby. The haemoglobin and haematocrit level was noted and compared between two groups using Mann-Whitney U test in SPSS 16 for Windows. Result: There were no difference on maternal characteristic between two groups, except for the maternal education and maternal economic status. The median neonatal haemoglobin level on DCC group was 15.77 g/dl and on ECC group was 14.36 g/dl. There was statically significant higher neonatal haemoglobin level on DCC group (p=0.005). The median neonatal haematocrit level was 44.1% on DCC group and was 43.35% on ECC group. There was no difference on neonatal haematocrit level between two groups (p=0.652). Conclusion: Delaying cord clamping until at least two minutes after delivery could increase haemoglobin level on newborn babies. Therefore, this method was suggested for every delivery in area where there is a risk of anemia in neonates such as Indonesia. [Indones J Obstet Gynecol 2012; 36-1:24-7] Keywords: delayed cord clamping, haemoglobin, haematocrit